Factors influencing career choice among Faculty of Business Management students in UiTM Malacca City Campus / Ummu Mubarakah Yusri - Yusri, Ummu Mubarakah (Faculty of Business and Management, 2019)
The aim of this study to investigate factors that influence career choice among Faculty of Business Management Students in UiTM Malacca City Campus. The variable involved are dependent and independent variables which is for dependent variable are career choice while for independent variable are family influence and personal interest. This study was conducted to know which one of the independent variables that significance towards career choice. The number of respondent involved in this study was 181 students. The data of this research was collected by questionnaire. Simple random techniques was used while distributing the questionnaire to respondent. As the result of the research, personal interest was found to be the dominant factors which have significance relationship towards career choice.